ANALISIS TOTAL PRODUCTIVE MAINTENANCE DENGAN METODE OEE DAN FMEA PADA MESIN EXTRUDER GW-350 - Dodi Siagian; Iwan Nugraha Gusniar; Iman Dirja (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2022)
An industrial company that specializes in plastics, with the basic ingredients of PolyEthylene Terephthalate, PolyPropylene, and Hight Impact Polystyrene, the product is a plastic plate that is produced through the operation of the Extruder machine. Total Productive Maintenance (TPM) is one method of analyzing a machine and will help research the effectiveness of a machine with the help of other methods such as Overall Equipment Effectiveness (OEE) and Failure Mode and Effect Analysis (FMEA). Based on the quantitative analysis of the OEE calculation, the OEE value of the Extruder 1 GW-350 machine is obtained with an average calculation of 79.35%. Based on qualitative analysis using FMEA, the RPN failure mode score on the Extruder 1 GW-350 engine was obtained. The highest RPN value is the printer is unstable (die) at 240.